Cho a, b, c khác 0. Tính D= $x^{2011}$ + $y^{2011}$ +$z^{2011}$ . Biết x, y, z thoả mãn $\frac{x^{2}+ y^{2} +z^{2}}{a^{2} + b^{2} +c^{2}}$ = $\fra

Question

Cho a, b, c khác 0. Tính D= $x^{2011}$ + $y^{2011}$ +$z^{2011}$ . Biết x, y, z thoả mãn $\frac{x^{2}+ y^{2} +z^{2}}{a^{2} + b^{2} +c^{2}}$ = $\frac{x^{2}}{a^{2}}$ + $\frac{y^{2}}{b^{2}}$ + $\frac{z^{2}}{c^{2}}$

in progress 0
Hưng Gia 1 year 2020-10-14T02:39:12+00:00 1 Answers 80 views 0

Answers ( )

    0
    2020-10-14T02:41:07+00:00

    Đáp án:

     

    Giải thích các bước giải:

     Từ giả thiết suy ra :

    ($\frac{x^2}{a^2}$- $\frac{x^2}{a^2+b^2+c^2}$) + ($\frac{y^2}{b^2}$- $\frac{y^2}{a^2+b^2+c^2}$) + ($\frac{z^2}{c^2}$- $\frac{z^2}{a^2+b^2+c^2}$) = 0

    ⇔$x^{2}$ ( $\frac{1}{a^2}$ – $\frac{1}{a^2+b^2+c^2}$) + $y^{2}$ ( $\frac{1}{b^2}$ – $\frac{1}{a^2+b^2+c^2}$) + $z^{2}$ ( $\frac{1}{c^2}$ – $\frac{1}{a^2+b^2+c^2}$) = 0 ( * )

    Do $\frac{1}{a^2}$ – $\frac{1}{a^2+b^2+c^2}$ > 0 

          $\frac{1}{b^2}$ – $\frac{1}{a^2+b^2+c^2}$ > 0 

          $\frac{1}{c^2}$ – $\frac{1}{a^2+b^2+c^2}$ > 0 

    nên từ ( * ) ⇒ x = y = z = 0 . Do đó M = 0 

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )